Recent Advances in Organocatalyzed Asymmetric Sulfa‐Michael Addition Triggered Cascade Reactions - Niu, Cheng; Du, Da‐Ming (Chemical record, 2023)
The sulfa‐Michael addition reaction is a crucial subset of the Michael addition reaction, and aroused the interest of numerous synthetic biologists and chemists. In particular, sulfa‐Michael addition triggered cascade reaction has developed quickly in recent years because it offers an efficient method to construct C−S bonds and other bonds in one approach, which is widely applicable for building chiral pharmaceuticals, their intermediates, and natural compounds. This review emphasizes the recent advancements in sulfa‐Michael addition‐triggered cascade reactions for the stereoselective synthesis of sulfur‐containing compounds, including sulfa‐Michael/aldol, sulfa‐Michael/Henry, sulfa‐Michael/Michael, sulfa‐Michael/Mannich and some sulfa‐Michael triggered multi‐step processes. Moreover, some reaction mechanisms and derivatization experiments are introduced appropriately. This review sumarizes the recent advances in sulfa‐Michael addition‐triggered cascade reactions for the stereoselective synthesis of sulfur‐containing compounds, including sulfa‐Michael/aldol, sulfa‐Michael/Henry, sulfa‐Michael/Michael, sulfa‐Michael/Mannich and some sulfa‐Michael triggered multi‐step process.